Structural biology of the core autophagy machinery. (April 2017) - Suzuki, Hironori; Osawa, Takuo; Fujioka, Yuko; Noda, Nobuo N
Highlights: Atg13 facilitates autophagy initiation complex formation and supramolecular assembly. Autophagy-specific phosphatidylinositol 3-kinase complex has a V-shaped architecture. Atg9 vesicles, with the help of the autophagy initiation complexes, form membrane source of autophagosomes. Abstract : In autophagy, which is an intracellular degradation system that is conserved among eukaryotes, degradation targets are sequestered through the de novo synthesis of a double-membrane organelle, the autophagosome, which delivers them to the lysosomes for degradation. The core autophagy machinery comprising 18 autophagy-related (Atg) proteins in yeast plays an essential role in autophagosome formation; however, the molecular role of each Atg factor and the mechanism of autophagosome formation remain elusive. Recent years have seen remarkable progress in structural biological studies on the core autophagy machinery, opening new avenues for autophagy research. This review summarizes recent advances in structural biological and mechanistic studies on the core autophagy machinery and discusses the molecular mechanisms of autophagosome formation.